Pengaruh Temperatur Larutan Triethylamine (Tea), Air dan Ca(OH) 2 terhadap Pelepasan CO 2 pada Proses Pemurnian Biogas - Kurniawan, Zulkifli; Wardana, ING; Widhiyanuriyawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Biogas is renewable fuel that generated by bacteria activities in anaÃ«robic organic matter process. Biogas composed by CH 4 17 (54% to 70%), CO2 (27% to 45%) and impurities gas such as N2 , H2O, CO, H2S. The CO2 on biogas should be reduced because itâ€™s as inhibitor that reduces heat of biogas flame. This research proposed to reduce CO 2 in the packed column purification system by using TEA, H2O, and Ca(OH)2 solution as absorber.The absorber temperature were variated 35o, 45o, 55omand 65oC for knowing performance absorber reduce CO2 at the flow rate of CO 2 and CH4 , entering packed collum by 0.1 l/m, release time of CO2 in heater was eight minutes by comparison CH4 , and CO2 i.e. 80 % -20 %, 85 % -15 %, 90 % -10 % and 95 % -5 %. The result of this study was the higher the temperature heating, the higher the percentage of CO2 released. Absorbentt TEA + H2O and combined TEA + H2O + Ca(OH)2 , improve absorption of CO2 in a linear manner at a temperature of warming 35, 45, 55, 65 c.Keywords : Biogas, Absorption, Temperature, TEA, H2O, Ca(OH)2